Improving Student's Management Ability with Developed Halma Media - Tri Hardono; - Suad; Sri Utaminingsih (Universitas Muhammadiyah Semarang, 2021)
Abstract. The purpose of this study was to develop learning media for the halma game to improve the ability to count multiples of a number for grade 4 SD in Demak Regency. This research method is Research and development. There are 3 stages in this research: the preliminary study stage, the development stage, media validation, and field testing, as well as the dissemination and socialization stage. The results of this study are in the form of manual learning media products in the form of multiples number board games from paper and MMT, and digital, in the form of digital in the form of a game application using articulate storyline 3. Validation from media experts and material experts gave assessments, validators I, II, III, and IV respectively 36, 35, 37, and 36 from a maximum score of 40. The media developed was categorized as very good. The results of the control class posttest t test and the experiment shows the value of t = -336 with a Sig. (2-tailed) value of 0.664> α = 0.05, so that the media developed is valid.Keywords: Checkers game, multiples of numbers